2019
DOI: 10.1074/jbc.ra119.009910
|View full text |Cite
|
Sign up to set email alerts
|

Ega3 from the fungal pathogen Aspergillus fumigatus is an endo-α-1,4-galactosaminidase that disrupts microbial biofilms

Abstract: Edited by Gerald W. HartAspergillus fumigatus is an opportunistic fungal pathogen that causes both chronic and acute invasive infections. Galactosaminogalactan (GAG) is an integral component of the A. fumigatus biofilm matrix and a key virulence factor. GAG is a heterogeneous linear ␣-1,4 -linked exopolysaccharide of galactose and GalNAc that is partially deacetylated after secretion. A cluster of five co-expressed genes has been linked to GAG biosynthesis and modification. One gene in this cluster, ega3, is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 90 publications
1
42
0
Order By: Relevance
“…8c) and are coregulated 5 . Recently, Ega3 was found to be specific for deacetylated regions of GAG supporting that agd3 and ega3 homologs are functionally linked 9 . Spherulin-4 annotated genes were also found in some of the Actinobacteria operons.…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 88%
See 1 more Smart Citation
“…8c) and are coregulated 5 . Recently, Ega3 was found to be specific for deacetylated regions of GAG supporting that agd3 and ega3 homologs are functionally linked 9 . Spherulin-4 annotated genes were also found in some of the Actinobacteria operons.…”
Section: Agd3 Contains a Unique Carbohydrate Binding Module (Cbm)mentioning
confidence: 88%
“…1) and includes the production of activated monosaccharide building blocks by the epimerase Uge3 5,7 followed by synthesis and export by the predicted integral membrane glycosyltransferase Gtb3 5 . The GAG cluster also encodes two glycoside hydrolases: an endoα-1,4-N-acetylgalactosaminidase, Sph3 6,8 ; and an endo-α-1,4galactosaminidase, Ega3 9 . Lastly, GAG is partially deacetylated by the secreted protein Agd3 and deletion of agd3 abolishes this modification 5 .…”
mentioning
confidence: 99%
“…Bamford et al [98] recently reported that Ega3 has endo-α-1,4-galactosaminidase activity, but the function of Ega3 during GAG biosynthesis is still unknown. The authors suggested that the N-terminal transmembrane region of Ega3 is cleaved, and then the mature Ega3 form is released from the membrane and hydrolyzes deacetylated GAG [98] (Fig. 3b).…”
Section: Gag Biosynthesismentioning
confidence: 99%
“…As observed in the latter, the EPS architecture within such multipartite consortia is jointly shaped and highly adapted to the demands of its inhabitants. Taking into account that each partner within collaborative microbial biofilms contributes its own set of enzymes involved in glycan synthesis and hydrolysis ( Bamford et al ., 2019 ), this could fuel the generation of unique community patterns. Therefore, it would be of great interest to understand whether such community-derived glycan signatures are relevant for microbiota assembly and plant recognition.…”
Section: Concluding Remarks and Perspectivementioning
confidence: 99%